SIFO 1989: The natural step_5 - Swedish Institute of Public Opinion Research; Det naturliga steget (Swedish Institute of Public Opinion Research, 1993)
This study was carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of an environmental campaign called ´Det naturliga steget´. The first interview took place before the campaign. Respondents were asked about their interest in environmental issues and how they get information about such issues; events the respondents felt anxious about during the last year, and to what extent they felt anxious about environmental pollution; opinion on the environmental situation now compared with 10 years ago, and if the pollution of the environment threatens the survival of mankind; the five most important causes of environmental pollution; concern about 20 different environmental problems and confidence in the way different groups handles the environmental issue; own activities during the last year to improve environment and changes one is prepared to do for improving the environment. Furthermore the respondents were asked if they agreed or disagreed with eight different statements concerning the environment. The knowledge of environmental issues was also tested by a battery of questions. The second interview was carried through after the accomplishment of the campaign. Many of the questions asked in the pre-campaign interview was also asked this time. New questions dealt with knowledge of the campaign. One part of the campaign consisted of a pamphlet and a tape sent to all households in Sweden. The respondents were asked about their usage of and attitude toward this information material. Background variables include information on age, housing, size of household, age of members of household, adult children moved out, car ownership, amount of money needed in household, personal income and household income, marital status, education, occupation, employed or self-employed, public or private sector, trade union membership, size of place of work, gender, Swedish citizenship and party preference.

Undersökningen genomfördes vid två tillfällen, en gång innan kampanjen "Det naturliga steget" genomfördes och en gång efter. Frågorna gällde bland annat oro under det senaste året, intresse för och kunskaper om miljöfrågor, orsaker till miljöproblem och hur orolig man är för olika miljöproblem. Andra frågor gällde förtroendet för olika grupper i samhället då det gäller miljöproblem och egna aktiviteter för att förbättra miljön. Den del av undersökningen som genomfördes efter kampanjen innehöll även frågor om hur man tagit del av programmet och hur man uppfattat det.
SIFO 1989: Det naturliga steget_2
Keywords: Information society; Informationssamhället; Environment and conservation; Miljö och naturvård; Social Sciences; Samhällsvetenskap